Pengaruh Media Sosial Terhadap Motivasi Belajar Mahasiswa Teknik Infromatika - Karolus W. Rato; Sarniyati Tanggela; Yohanes Beru; Junari S. Dendo; Jenita S. Ngongo; Kornelis P. Bali (Pusat Riset dan Inovasi Nasional, 2024)
Technological developments that occur in modern times like today have made us accustomed to using technology that makes everything easy and fast in doing many things, for example in the world of information and communication. Currently, the most important media and has the most extensive network is the internet. This internet media is developing very rapidly and always provides innovation to its users according to current needs. This case study aims to see the influence that the use of social media has on the learning motivation of Stella Maris Sumba University Students. Students are individuals who are easily influenced by both the environment and the people around them, it is even a student's responsibility to be influenced by various surrounding environments. The author tries to research students' learning motivation, because without learning motivation, students will not carry out their obligations as students. For the author, this is very interesting, because motivation is very important for individuals to do something. Because without motivation an individual will not be able to do anything, there is no encouragement or stimulation that moves the individual to do something